2010
DOI: 10.1021/ol101592r
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed C−O Activation of Phenol Derivatives with Potassium Heteroaryltrifluoroborates

Abstract: A general method based on nickel-catalyzed C–O activation of various phenol derivatives with potassium (hetero)aryltrifluoroborates has been developed. A large number of heterobiaryls can be easily obtained with yields up to 99% using methanesulfonate cross-coupling partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 31 publications
3
55
0
1
Order By: Relevance
“…199 Model studies with electrophiles derived from 2-naphthol utilizing 10 mol% Ni(COD) 2 and 20 mol% PCy 3 HBF 4 in 1:1 t -BuOH/H 2 O provided an order of reactivity of OMs>OTs~OSO 2 NMe 2 >OPiv>OBoc>OCONE 2 >OBz>>OMe = 0. Given these reactivity trends, cost-effective aryl mesylates were chosen as the primary electrophillic substrate.…”
Section: Nickel-catalyzed Reactions Of Aryl and Vinyl Sulfonates Amentioning
confidence: 98%
“…199 Model studies with electrophiles derived from 2-naphthol utilizing 10 mol% Ni(COD) 2 and 20 mol% PCy 3 HBF 4 in 1:1 t -BuOH/H 2 O provided an order of reactivity of OMs>OTs~OSO 2 NMe 2 >OPiv>OBoc>OCONE 2 >OBz>>OMe = 0. Given these reactivity trends, cost-effective aryl mesylates were chosen as the primary electrophillic substrate.…”
Section: Nickel-catalyzed Reactions Of Aryl and Vinyl Sulfonates Amentioning
confidence: 98%
“…Other Pd sources such as Pd(OAc) 2 and Pd 2 (dba) 3 were much less effective as shown in entries 8–10. Phosphane‐derived nickel complexes, such as NiCl 2 (PCy 3 ) 2 have been demonstrated as the most effective catalysts to carry out the Suzuki coupling of phenol derivatives in organic solvents 6c. However, the coupling between imidazolylsulfonate 2aa and potassium phenyltrifluoroborate catalyzed by NiCl 2 (PCy 3 ) 2 , led to a negligible reaction conversion (Table 1, entry 11).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we also tested the reactivity of the electrophiles 2ab , 2ac , 2ad , 2ae , and 2af in the process under the optimized reaction conditions. As depicted in entries 12–16, none of these derivatives showed any reactivity and only starting material was recovered from the crude reaction mixture 24,25…”
Section: Resultsmentioning
confidence: 99%
“…Molander demonstrated that potassium trifuluoroborate salts can also serve as effective coupling partners for the nickel-catalyzed cross-coupling of aryl pivalates and carbamates [49]. A nickel complex having a pincer-type ligand was shown to be a viable catalyst precursor, when used in conjunction with PCy 3 , for the Suzuki-Miyaura type cross-coupling of hindered 9-anthracenyl pivalates [50].…”
Section: Suzuki-miyaura Type Reactionsmentioning
confidence: 99%
“…A nickel complex having a pincer-type ligand was shown to be a viable catalyst precursor, when used in conjunction with PCy 3 , for the Suzuki-Miyaura type cross-coupling of hindered 9-anthracenyl pivalates [50]. Aryl carbonates have also been reported to undergo crosscoupling with organoboron compounds in the presence of NiCl 2 (PCy 3 ) 2 [44] or Ni(cod) 2 /PCy 3 catalysts (cod = 1,5-cyclooctadiene) [49]. Interestingly, Kuwano reported that a bidentate ligand DCyPF [1,1-bis(di-cyclohexylphosphino)ferrocene] can also serve as an effective ligand for the nickel-catalyzed crosscoupling of aryl carbonates with arylboronic acids [51].…”
Section: Suzuki-miyaura Type Reactionsmentioning
confidence: 99%